Nexus between energy pricing and carbon emission. A policy mix response of developing economies. Issue 1 (31st December 2022) - Yuan, Miao; Hu, Hele; Alharthi, Majed; Ahmad, Ishtiaq; Abbas, Qaiser; Taqi, Muhammad
Abstract: The study utilised a data set of South Asian countries of energy pricing (E.P.), carbon emission, and policy mix between 1990 and 2020. A comprehensive set of models from econometric such as fixed effect (F.E.), and panel quantile regression (P.Q.R.) is used to determine the relationship between underline indicators. Furthermore, the T.O.P.S.I.S. method from operational research was applied to determine the efficiency level of these factors in the South Asian region. E.P. and carbon emission are contributing positively to the process of household consumption (H.C.). In the policy mix scenario, H.C. is positively associated with inflation while negatively with the tax rate. Furthermore, the outcomes of the T.O.P.S.I.S. indicate that Bhutan is performing efficiently in the said parameters followed by Pakistan, while India's performance is not impressive in this regard. This study can be helpful to policymakers for effective energy demand planning, conservation, and frame policies that would ensure sustainable H.C. and serve as motivation to search for alternative energy sources to meet the growing energy demand.